2014
DOI: 10.1186/1471-2164-15-750
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of replication-independent endogenous double-strand breaks in Saccharomyces cerevisiae

Abstract: BackgroundReplication-independent endogenous double-strand breaks (RIND-EDSBs) occur in both humans and yeast in the absence of inductive agents and DNA replication. In human cells, RIND-EDSBs are hypermethylated, preferentially retained in the heterochromatin and unbound by γ-H2AX. In single gene deletion yeast strains, the RIND-EDSB levels are altered; the number of RIND-EDSBs is higher in strains with deletions of histone deacetylase, endonucleases, topoisomerase, or DNA repair regulators, but lower in stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Second, we observed accumulation of replication-independent endogenous DNA double strand breaks (RIND-EDSBs) in hypermethylate genome [42]. Our recent study indicated that RIND-EDSBs may possess an epigenetic role in reducing DNA strain similar to a small gap between two railway lines [43][44][45]. Third, DNA repair activity is different depending on chromatin structure [46,47].…”
Section: Discussionmentioning
confidence: 90%
“…Second, we observed accumulation of replication-independent endogenous DNA double strand breaks (RIND-EDSBs) in hypermethylate genome [42]. Our recent study indicated that RIND-EDSBs may possess an epigenetic role in reducing DNA strain similar to a small gap between two railway lines [43][44][45]. Third, DNA repair activity is different depending on chromatin structure [46,47].…”
Section: Discussionmentioning
confidence: 90%
“…Instead, they may possess important biological functions, perhaps in relieving topological stress that might otherwise result in uncontrolled DNA breakage. They have also been reported to occur nonrandomly, for example, with an increased frequency in heterochromatin (200). Such breaks are repaired by either Ku-or Rad51p-dependent pathways, as evidenced by the increased levels of such breaks in cells deleted for either Ku or Rad51p (201).…”
Section: Hmo1 and Dna Double-strand Break Repairmentioning
confidence: 97%
“…The yeast strains used in this study were obtained from the Haber Laboratory (Charlestown, MA, USA) (37) and included JKM115 [MAT-a DhohmlD::ADE1 () hmrD::ADE1 lys5 leu2 ura3 trp1], JKM179 [MAT-a DhohmlD::ADE1 hmrD::ADE1 lys5 leu2 ura3 trp1 ade3::GALHO (HO nuclease gene regulated by the GAL1 promoter)], BY4741, ypr052cΔ (nhp6aΔ), and YAA25 (+ HO, mec1D sml1D), as previously described (14,15). For chronological aging experiments, yeast cells were grown in yeast peptone (YP) medium + 2% glucose at 30°C on a rotary shaker at 250 rpm overnight and then switched to YP medium + 2% raffinose for 2 d before being washed and resuspended in sterile deionized water.…”
Section: Yeast Strains Media and Growth Conditionsmentioning
confidence: 99%
“…As previously described (15), ligated HMW DNA was digested with RsaI and ligated again with the second linkers. The HMW DNA was subjected to PCR with 2 primers of each linker.…”
Section: Library Preparation and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation